Relationship of dietary energy and heat tolerance in sheep - Karim, S A; Patyanak, B C (The Indian Journal of Animal Sciences, 2012)
Relationship between dietary energy and heat tolerance of Mutton synthetic rams was assessed by feeding them on 100 % of their maintenance energy requirement under shed (G1) and solar exposure (G2) or 115 (G3) and 130 (G4)% of their energy requirement under summer sun. DMI was similar in all the groups as per experimental design whereas water consumption was higher in G3 compared to G1, G2 and G4. The rams exposed to heat had average water consumption of 11.5 % of body weight amounting to 6.23 I/kg DMI. The respiration frequency (RF) registered usual variation increasing by 210 % from morning to peak hot period (PHP) in these heat exposed rams. Such increase in RF was of lower magnitude in animals under protection compared to solar exposed groups and the trends remained same on its expression in terms of unit rise in rectal temperature (RT). The RF in the 2 recordings and its increase for unit Â°C rise in RT was higher (P